"Critical statistical literacy", "Social justice statistics", and "Critical statistical consciousness" as higher education imperatives, amidst the COVID-19 pandemic in South Africa - Krishnannair, A.; Krishnannair, S. (South African Journal of Higher Education, 2022)
Familiarity with the Covid-19 pandemic-related statistical jargon is a requirement for the layman, who must stay abreast of developments apropos of rate of infection, spread, and mortality rate comprising the pandemic. Such a familiarity, termed statistical literacy (SL) in the related discourse, is increasingly becoming an important aspect of higher education (HE) studentship across universities, internationally. This article offers an extension to the extant theorisations of statistical literacy in the context of Covid-19. Formulation of a solid theoretical rationale for fostering the competency of SL at the HE level is therefore central to this article. The literature offers the notion of critical statistical literacy (CSL) as anchored in a social-justice paradigm. CSL is used here as a starting point for the theoretical extensions proposed in this article. A novel disciplinary idea called “social justice statistics (SJS)” is also introduced. The idea of “critical statistical consciousness (CSC)” as a new proposition for theorising the statistical sensibility of citizens is also put forward. The ways in which CSC rationalises CSL, and foregrounds SJS, are subsequently theorised. CSC, as a broad attribute, quality, or a higher-education trait, is thus positioned in the context of the Covid-19 pandemic. These theorisations have implications for the practice of statistics, both at the levels of “producer” and “consumer” of statistical communications that characterise the way in which the pandemic is understood by the layman.